Silicide coatings structure optimization based on multiscale approach - Lytovchenko, S.V.; Beresnev, V.M.; Chyshkala, V.A.; Dmytrenko, A.Ye.; Nyemchenko, U.S.; Burkovska, V.V. (Физическая инженерия поверхности, 2013)
This paper is an attempt to apply the multi-scale approach to the study of silicide coatings on molybdenum. Macro- and microstructure of silicide coatings largely determines mechanical and corrosion properties of molybdenum-protective coating composites. To prevent unacceptable changes, it is necessary to foresee the evolution of structure during formation of the coating and during operation of the composite. This paper analyzes the factors that determine degradation of properties of the coatings at different hierarchical levels. The requirements for the macro- and microstructure of the silicides with a view to achieving better thermal properties of the protective coating have been formulated.